Dehydration of green beans using ultrasound-assisted vacuum drying as a novel technique: drying kinetics and quality parameters - Tekin, Zeynep Hazal; Baslar, Mehmet; Karasu, Salih; Kilicli, Mahmut (WILEY, 2017)
The ultrasound-assisted vacuum (USV) drying technique is a novel method and ultrasonic treatment under vacuum causes to accelerate the dehydration rate of food materials. This study compared the drying kinetics and some quality parameters for green beans subjected to USV, oven, and vacuum drying at 55, 65, and 75 degrees C. The drying time was shortened by around 1 hr using USV at each temperature. Effective moisture diffusivity values was found between 2.00 x 10(-10)-4.81 x 10(-10) m(2) s(-1) and it was increased compared with control treatment between 8.9% and 24.5%. USV treatment resulted phenolic compounds compared with unsonicated control. However, USV caused more color change than the control, oven and vacuum. Lower the total color difference values were obtained for samples dehydrated by vacuum dryer. USV had greater advantages compared with the control and it can potentially be applied to green beans and other vegetables for faster drying processing. Practical applicationsThis study exhibit the usability of ultrasound-assisted vacuum dehydration to increase the drying rate, to improve the energy efficiency of the drying process and to develop quality of the final products. The results indicated that ultrasound treatment could be used as an assistant technique to accelerate drying rate and improve product quality. Besides mathematical models and drying kinetic, this study presents useful information about the different dehydration process for green bean. It was expected that this study will great contribution to literature, food science and technology.
Keywords: color; drying kinetics; green beans; phenolic compounds; ultrasound-assisted vacuum drying; ANTIOXIDANT ACTIVITY; OSMOTIC DEHYDRATION; BIOACTIVE COMPOUNDS; PHENOLIC-COMPOUNDS; SLICES; FRUITS; Food Science & Technology